Assessment of tenant satisfaction with public housing in Johor Bahru - Fatin Aziz, 1986- , author; Ahmad Ariffian Bujang, supervisor; Fakulti Geoinformasi dan Harta Tanah (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Sains (Harta Tanah)) - Universiti Teknologi Malaysia, 2017